Anti‐biofilm and sporicidal activity of peptides based on wheat puroindoline and barley hordoindoline proteins. (30th May 2016) - Shagaghi, Nadin; Alfred, Rebecca L.; Clayton, Andrew H. A.; Palombo, Enzo A.; Bhave, Mrinal
Abstract : The broad‐spectrum activity of antimicrobial peptides (AMPs) and low probability of development of host resistance make them excellent candidates as novel bio‐control agents. A number of AMPs are found to be cationic, and a small proportion of these are tryptophan‐rich. The puroindolines (PIN) are small, basic proteins found in wheat grains with proposed roles in biotic defence of seeds and seedlings. Synthetic peptides based on their unique tryptophan‐rich domain (TRD) display antimicrobial properties. Bacterial endospores and biofilms are highly resistant cells, with significant implications in both medical and food industries. In this study, the cationic PIN TRD‐based peptides PuroA (FPVTWRWWKWWKG‐NH2 ) and Pina‐M (FSVTWRWWKWWKG‐NH2 ) and the related barley hordoindoline (HIN) based Hina (FPVTWRWWTWWKG‐NH2 ) were tested for effects on planktonic cells and biofilms of the common human pathogens including Pseudomonas aeruginosa, Listeria monocytogenes and the non‐pathogenic Listeria innocua . All peptides showed significant bactericidal activity. Further, PuroA and Pina‐M at 2 × MIC prevented initial biomass attachment by 85–90% and inhibited >90% of 6‐h preformed biofilms of all three organisms. However Hina, with a substitution of Lys‐9 with uncharged Thr, particularly inhibited Listeria biofilms. The PIN based peptides were also tested against vegetative cells and endospores of Bacillus subtilis . The results provided evidence that these tryptophan‐rich peptides could kill B. subtilis even in sporulated state, reducing the number of viable spores by 4 log units. The treated spores appeared withered under scanning electron microscopy. The results establish the potential of these tryptophan‐rich peptides in controlling persistent pathogens of relevance to food industries and human health. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Drug‐resistant pathogens and persistent infections are a serious concern worldwide. This study shows that tryptophan‐rich antimicrobial peptides (AMPs), designed based on wheat puroindoline proteins, are highly effective against biofilms of Pseudomonas aeruginosa and Listeria monocytogenes and endospores of Bacillus subtilis . The results establish their potential as novel biocidal agents.